PERCERAIAN MASSAL DI ACEH: KAJIAN FENOMENOLOGI JEJAK JUDI ONLINE DI BALIK CANGKIR KOPI - Auliya, Yunysa (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2025)
This study aims to analyze the role of warkop (coffee shops) as facilitators of online gambling and its correlation with the phenomenon of mass divorce in Aceh. Employing a qualitative method with a library research approach, this study collected and analyzed data from various relevant literatures. The findings indicate a significant increase in divorce rates in Aceh, predominantly initiated by wives, with online gambling as a primary trigger due to husbands' inability to provide financial support and continuous marital conflicts. Coffee shops have transformed into gambling arenas, exacerbating family financial and emotional problems, which directly lead to disputes and divorce. The conclusion highlights that online gambling fundamentally erodes family resilience, necessitating proactive prevention efforts through premarital guidance and inter-agency collaboration to strengthen family foundations and reduce divorce rates.